USE OF TECHNOLOGIES IN EDUCATION AND PROMOTION OF ORAL HEALTH - Neves de Souza, Kathianna; Neves de Souza Bibiano, Raquel (Health and Society, 2023)
This study sought to investigate the use of educational technologies and their importance in acquiring knowledge about hygiene and oral health. For greater structuring and knowledge, a literature review was carried out, based on searches in articles, dissertations, theses, and specialized journals. The general objective of this article was to analyze the importance of using digital technologies and their contributions to students’ education and oral hygiene. For greater reliability regarding what was proposed to be researched in this work, qualitative research was carried out, and the type of study that best fit the proposal was descriptive research. Based on the results found throughout the study period on the topic discussed, the results indicated that the use of educational technologies works as an important ally, as it allows teachers to use a different way of promoting knowledge to their students. It is noteworthy that health education is of paramount importance for the student. It is notably known that schools play an important role in society and they also have the duty to teach not only the contents of the curriculum, but also to promote health education. It is noteworthy that schools must use digital technologies in their actions and methodologies to facilitate the student’s teaching-learning process, as in this way the most common oral diseases among students can be fully prevented. It is noteworthy that carrying out educational activities and actions on oral health promotes better therapeutic results, regardless of the technology used. Digital technologies can function as facilitators in the student’s teaching-learning process. However, the results point in a direction that indicates that it can be a promising instrument to improve adherence and motivation of Mental Health patients.